Review of the fish-parasitic genus Ceratothoa Dana, 1852 (Crustacea: Isopoda: Cymothoidae) from Australia, with description of two new species - Martin, Melissa B.; Bruce, Niel L.; Nowak, Barbara F. (Zootaxa, 2015)
The genus Ceratothoa Dana, 1852, is revised for Australian waters. Ceratothoa is represented in Australia by nine species, including two new species: Ceratothoa barracuda sp. nov. described from Cairns and Ceratothoa globulus sp. nov. described from Lord Howe Island. Ceratothoa imbricata Fabricius, 1775 is redescribed, with Ceratothoa trillesi (Avdeev, 1979) and Ceratothoa huttoni Filhol, 1885 placed into junior synonymy; the preferred hosts are species of the genus Trachurus (Carangidae). Ceratothoa banksii (Leach, 1818) is validated and brought out of synonymy with Ceratothoa imbricata; host species are from the families Kyphosidae, Scombridae, Latridae, Carangidae, Mugilidae, Salmonidae, Scatophagidae, Pomatomidae and Hemiramphidae. Species excluded from the Australian fauna are Ceratothoa trigonocephala (Leach, 1818) with an unknown host identity and type locality; and Ceratothoa lineata Miers, 1876a, that here is transferred to the genus Mothocya Costa, 1851, with Mothocya ihi Bruce, 1986 placed into junior synonymy. Ceratothoa contracta (Miers, 1880), the New Zealand Ceratothoa novaezelandiae Filhol, 1885 and the East Pacific Ceratothoa gaudichaudii (Milne Edwards, 1840) are regarded here as species inquirenda. A key to the Australian species of Ceratothoa is presented.